PENGARUH PEMBERIAN FRAKSI LARUT AIR EKSTRAK ETANOLIK PISANG KAPAS (Musa paradisiaca L.) TERHADAP KADAR GLUKOSA DARAH SECARA IN VIVO DAN PELACAKAN SENYAWA AKTIFNYA - Nunung Yuniarti; Rina Nur Maulawati; Suwijiyo Pramono (Majalah Obat Tradisional, 2014)
Banana is one of Indonesian food which has many pharmacological activities. Pisang kapas (Musa paradisiaca L.), one of Indonesian banana, is well known empirically as laxative, so it can be used in the treatment of constipation. It has been reported that both of chloroformic and ethanolic extract of pisang kapas have antidiabetic activities. However, fractination of those are not yet performed and report about their antidiabetic activities are not yet available. Here we investigated the effect of water-dissolved fraction of ethanolic extract of cotton banana to reduce the blood glucose level in rat model and identified its active ingredient. The oral glucose tolerance method with 60 min glucose loading time was used to induce hyperglicemic condition in rats, either in control group or treatment group. Glibenclamid (positive control), sodium carboxymethyl cellulose (negative control) and the fraction were orally given to the rats in a single dose. To measure blood glucose level photometrically, enzimatic reaction by using diagnostic reagent Glucose GOD FS is applied. Paper chromatography was utilized to identify the ingredient of the fraction qualitatively.  The fraction in dose of 0.25 g/kg reduced blood glucose level by 22.28 ± 0.76 %. The fraction contained reductants in addition to glucose, amino acids, and the acids in plants.